Identification of small molecule inhibitors of human COQ7. Issue 1 (1st January 2020) - Tsuganezawa, Keiko; Sekimata, Katsuhiko; Nakagawa, Yukari; Utata, Rei; Nakamura, Kana; Ogawa, Naoko; Koyama, Hiroo; Shirouzu, Mikako; Fukami, Takehiro; Kita, Kiyoshi; Tanaka, Akiko
Graphical abstract: Highlights: The pathogenesis of ubiquinone (UQ) deficiency syndrome is largely unknown. We have developed human COQ7 inhibitors that interfere with UQ synthesis. The highly potent compounds do not disturb growth of human normal culture cells. The inhibitors will be useful for studying the UQ supplementation pathways. Abstract: Given that the associated clinical manifestations of ubiquinone (UQ, or coenzyme Q) deficiency diseases are highly heterogeneous and complicated, effective new research tools for UQ homeostasis studies are awaited. We set out to develop human COQ7 inhibitors that interfere with UQ synthesis. Systematic structure-activity relationship development starting from a screening hit compound led to the identification of highly potent COQ7 inhibitors that did not disturb physiological cell growth of human normal culture cells. These new COQ7 inhibitors may serve as useful tools for studying the balance between UQ supplementation pathways: de novo UQ synthesis and extracellular UQ uptake.